The riddle of recurrent fever: a clinical approach to pediatric autoinflammatory diseases - Meertens, B.; Hoste, L.; Tavernier, S. J.; Haerynck, F. (Frontiers in Pediatrics, 2024)
Autoinflammatory diseases (AIDs) are a group of immunodysregulatory disorders resulting in the increased release or signaling of pro-inflammatory cytokines. Patients with AIDs present systemic inflammation in sterile conditions, which are mainly caused by defects in the innate immune system. Fever is one of the typical symptoms of this derailed immune signaling. In addition, autoinflammatory diseases manifest with varying other symptoms during flare-ups and interphasic periods. The diagnosis of these rare diseases poses numerous challenges. This paper provides an overview of AIDs that arise in childhood and in which fever commonly presents as a symptom. It outlines clinical signs, pathophysiology, diagnosis, and management for each syndrome. Additionally, we discuss a comprehensive diagnostic approach for children where an AID is suspected.